Analysis the Aspect of Higher Order Thinking Skill on Fungi Content Assesment Instrument for Senior High School Grade 10 - Haryanto Haryanto; Yuni Ahda; Rahmawati Darussyamsu (ATRIUM PENDIDIKAN BIOLOGI, 2018)
ABSTRACT High order thinking skills is very important based 2013 Curriculum in Indonesia. High order thinking skills need to be developed so that learners not only receive the information provided, but can use it and convert it into new information to solve the problems they face. The type of research used is descriptive research, by collecting data in the form of assessment instruments used by teachers in assessing the learning process. The assessment instruments on fungi material made by teachers for daily tests are generally still at the C1-C3 cognitive level (C1 is 40%, C2 is 46,7% and C3 is 13,3%), whereas high order thinking skills can be trained by providing an assessment instrument that is at the C4-C6 level of cognition in learning. Researchers analyze students by processing student's value data when answering C1-C3 problem commonly used by biology teacher in school and the result of the average score of learners did not experience problems, but the result of the analysis of learners with the provision of high ability thinking ability showed not yet capable of students answer about high-order thinking skills. This is evidenced by the test results obtained in the form of the average value of the class that is 28.15. Therefore, the assessment instrument used by the teacher has not been able to measure the high order thinking ability of the learners.